The role of primary school teachers' nutrition training in healthy eating promotion. (August 2022) - Marconi, Silvia; Vezzoli, Marika; Locatelli, Mara; Bertolotti, Paola; Zanini, Barbara; Valerio, Alessandra
Background: The prevalence of overweight and obesity in childhood makes intervention imperative, and schools provide a privileged setting in which to undertake this work. Teachers have the potential to influence children's eating behaviour through nutrition education and by acting as positive role models. We conducted a case–control study in 14 primary schools in Italy to assess the impact of a nutrition training programme (NTP) for primary school teachers on school children's eating habits. Methods: From participating schools, 11 volunteer teachers attended the NTP (trained teachers; TT), and as a control, we identified a group of teachers (untrained teachers; UT) who did not attend the NTP but who were interested in participating in the study. The effect of NTP intervention was evaluated on 599 children in the TT group and 536 in the UT group, respectively, using the KidMed questionnaire to assess adherence to a Mediterranean diet. Results: Overall adherence to a Mediterranean diet was low in 24.3%, medium in 56.6% and high in 19.1% of the children's population, with an overall median score of 5 (−3 to 12). Compared with the UT group, children in the TT group had a significantly higher adherence to a Mediterranean diet (Wilcoxon test p -value = .012) and showed significantly healthier habits regarding fast-food consumption, the eating of sweets and breakfast composition. Conclusions: Study findings demonstrate the efficacy of an indirect intervention for primary school children through intensive nutrition training for teachers. When planning future nutrition education in primary school, the role models offered by teachers should drive the interventions developed.